Contribution of Teacher Guidance and Counseling in the Implementation of Character Education Program in SMP Negeri 1 Percut Sei Tuan - Siti Hadijah Lubis; Lahmuddin Lubis; Nurussakinah Daulay (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to determine (1) the state of the character of students in SMP Negeri 1 Percut Sei Tuan (2) teacher guidance and counseling programs in implementing character education programs at SMP Negeri 1 Percut Sei Tuan (3) the role of guidance and counseling teachers in implementing the program. Character education at SMP Negeri 1 Percut Sei Tuan (4) the contribution of guidance teachers in the implementation of character education programs at SMP Negeri 1 Percut Sei Tuan. The type of research used in this thesis uses qualitative research. The subjects in this study were guidance and counseling teachers at SMP Negeri 1 Percut Sei Tuan, totaling 5 people. The data collection techniques used are interviews (interviews), observations (observations) and documentation. While the data analysis techniques used are data reduction, data presentation and drawing conclusions. The results of this study found that guidance and counseling teachers at SMP Negeri 1 Percut Sei Tuan were able to show an active role in the implementation of character education programs in schools through guidance and counseling services based on recommendations from the homeroom. Based on the results of interviews conducted by researchers with school principals, guidance and counseling teachers, they apply counseling guidance services through individual guidance, individual counseling, classical guidance, and group guidance, for students who undergo sanctions due to violations. Guidance and counseling teachers also collaborate with homeroom teachers, students and parents. The role of guidance and counseling teachers through comprehensive guidance and counseling services. Service quality can be improved through scheduling to meet student needs and respond to student problems through guidance and counseling programs and services.